Which expression is equivalent to (2 + 3) + 5?
2 answers:
A is the right answer 3+5 is 8 plus 2 is 10. 2+3 is 5 plus 5 is 10
The answer is A
Because 2 + 3 + 5 = (2 + 3) + 5 which is the same as saying 5 + 5.
Both equations = 10
You might be interested in
Answer: the answer would be s(9+4)
Step-by-step explanation:
![\dfrac{x^2+7x+1}{x^2+2x-15}=\dfrac{x^2+7x+1}{(x+5)(x-3)}](https://tex.z-dn.net/?f=%5Cdfrac%7Bx%5E2%2B7x%2B1%7D%7Bx%5E2%2B2x-15%7D%3D%5Cdfrac%7Bx%5E2%2B7x%2B1%7D%7B%28x%2B5%29%28x-3%29%7D)
which is undefined when
![x=-5](https://tex.z-dn.net/?f=x%3D-5)
or
![x=3](https://tex.z-dn.net/?f=x%3D3)
. The answer is then the third choice.
Answer:
The answer is x=20
Step-by-step explanation:
27-7=20
x=20
Answer: 4.71
Step-by-step explanation:
I don’t think you can lol